(6 x 10 ^ -3) ÷ (2 x 10 ^ -6) in standard form PLZ ANSWER QUICK

Question

(6 x 10 ^ -3) ÷ (2 x 10 ^ -6) in standard form PLZ ANSWER QUICK

in progress 0
Thông Đạt 2 weeks 2021-07-20T04:44:17+00:00 2 Answers 3 views 0

Answers ( )

    0
    2021-07-20T04:45:42+00:00

    Answer:

    Step-by-step explanation:

    0.006 / 0.000002 = 3000

    0
    2021-07-20T04:46:03+00:00

    Answer:

    3,000

    Step-by-step explanation:

    \frac{6*10^{-3} }{2*10^{-6} } =3*10^{-3+6}=3*10^{3} = 3,000\\

    We have:

    \frac{a^{x} }{a^{y} } = a^{x-y}

    In this case: \frac{10^{-3} }{10^{-6} } = 10^{(-3)-(-6)}  =10^{-3+6)} =10^3=1,000

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )